Hydrogen gas improves left ventricular hypertrophy in Dahl rat of salt-sensitive hypertension. (19th May 2019) - Matsuoka, Hiroki; Miyata, Seiko; Okumura, Nozomi; Watanabe, Takuya; Hashimoto, Katsunori; Nagahara, Miki; Kato, Kazuko; Sobue, Sayaka; Takeda, Kozue; Ichihara, Masatoshi; Iwamoto, Takashi; Noda, Akiko
ABSTRACT: Purpose : Hypertension is an important risk factor for death resulting from stroke, myocardial infarction, and end-stage renal failure. Hydrogen (H2 ) gas protects against many diseases, including ischemia-reperfusion injury and stroke. The effects of H2 on hypertension and its related left ventricular (LV) function have not been fully elucidated. The purpose of this study was to investigate the effects of H2 gas on hypertension and LV hypertrophy using echocardiography. Methods : Dahl salt-sensitive (DS) rats were randomly divided into three groups: those fed an 8% NaCl diet until 12 weeks of age (8% NaCl group), those additionally treated with 2% H2 gas (8% NaCl + 2% H2 group), and control rats maintained on a diet containing 0.3% NaCl until 12 weeks of age (0.3% NaCl group). H2 gas was supplied through a gas flowmeter and delivered by room air (2% hydrogenated room air, flow rate of 10 L/min) into a cage surrounded by an acrylic chamber. We evaluated interventricular septal wall thickness (IVST), LV posterior wall thickness (LVPWT), and LV mass using echocardiography. Results : IVST, LVPWT, and LV mass were significantly higher in the 8% NaCl group than the 0.3% NaCl group at 12 weeks of age, whereas they were significantly lower in the 8% NaCl + 2% H2 group than the 8% NaCl group. There was no significant difference in systolic blood pressure between the two groups. Conclusion : Our findings suggest that chronic H2 gas inhalation may help prevent LV hypertrophy in hypertensive DS rats.